2012
DOI: 10.1113/expphysiol.2012.067074
|View full text |Cite
|
Sign up to set email alerts
|

Time course of hepatic gluconeogenesis during hindlimb suspension unloading

Abstract: New Findings What is the central question of this study?The rate of liver gluconeogenesis during hindlimb suspension unloading has not been determined. What is the main finding and its importance?Hepatic gluconeogenesis is significantly increased under conditions of hindlimb suspension unloading, which simulates the muscular atrophy occurring during spaceflight. This finding supports earlier hypothesis. This metabolic shift in the living animal warrants further study. The goal of this work was to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
2
8
0
1
Order By: Relevance
“…This model has demonstrated that long-term weightlessness can cause systemic organ damages, such as bone loss, bone fracture, muscle loss and atrophy, cardiovascular disorders, and renal dysfunction [ 8 13 ]. Simulated weightlessness can decrease hepatic glycogen and increase hepatic gluconeogenesis [ 14 , 15 ]. Space flight can cause significant effects on liver glycogen, lipids, and enzymes in rats [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This model has demonstrated that long-term weightlessness can cause systemic organ damages, such as bone loss, bone fracture, muscle loss and atrophy, cardiovascular disorders, and renal dysfunction [ 8 13 ]. Simulated weightlessness can decrease hepatic glycogen and increase hepatic gluconeogenesis [ 14 , 15 ]. Space flight can cause significant effects on liver glycogen, lipids, and enzymes in rats [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The liver is one of the major metabolic organs in the control of systemic glucose homeostasis (47). Hepatic gluconeogenesis, as measured by transcription of key enzymes or incorporation of deuterated water into C-H bonds of newly synthesized glucose, was elevated in HU rats as early as 3 d after the initiation of HU (10,11). We also found up-regulated transcription of phosphoenolpyruvate carboxykinase 1, a key enzyme in gluconeogenesis, in the liver of HU mice (Fig.…”
Section: Inflammation and Impaired Glucose Metabolism In The Liver Comentioning
confidence: 57%
“…Altered glucose and lipid metabolism have been observed in humans and rodents during short-or long-term spaceflights (1)(2)(3)(4)(5). Glucose intolerance and insulin resistance are also identified in ground-based microgravity analogs, such as head-down bed rest and dry immersion in human volunteers and hind limb unloading (HU) in rodents (2,3,(6)(7)(8)(9)(10)(11)(12). Although the clinical significance remains to be fully determined, these metabolic changes may contribute to muscular atrophy, bone loss, and cardiovascular disorders under simulated or real microgravity (3,13).…”
mentioning
confidence: 99%
“…67 It is noteworthy that, although such calls are heard at regular intervals in European scholarship, European scholars have balked at effectively putting forward new frameworks or paradigms meant to revolutionize the way we look at international organizations. 68 In that sense, such calls have remained rather 'romantic'.…”
Section: Dmentioning
confidence: 99%